PENGEMBANGAN ALAT PERAGA MATEMATIKA INTERAKTIF BERBASIS AUGMENTED REALITY (AR) UNTUK VISUALISASI MATERI LUAS PERMUKAAN PADA BANGUN RUANG - Siti Rahila Fitria; Nurrizqa Nurrizqa (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2026)
Understanding the consept of surface area in geometry remains a challenge in mathematics learning, particularly due to students limited spatial visualization skills. This study aims to develop an interactive mathematics teaching aid based on Augmented Reality (AR) technology in the form of a mobile application. The development followed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and resulted in an application featuring 3D visualizations, interactive nets of geometry, and audio explanations for four types of solids cube, cuboid, triangular prism, and cylinder. The application was validated by two media experts and two subject matter experts, and tested on seventh grade students of MTS Muta’alimin. The media expert validation showed a feasibility score of 82,5% (highly feasible category), the subject matter expert validation scored 92,5% (highly feasible category), and the student trial obtained an average score of 93,7% (highly feasible category). Based on these results, the application is considered highly feasible as an interactive learning media that effectively supports students in understanding surface area concepts in a more engaging and meaningful way.